[KUBINEC, M. 2022. Obchodná spoločnosť v kríze. 1. vydanie. Praha : C. H. Beck, 184 s.] - Slezáková, Andrea, 1980-
Recenzia na vedeckú monografiu doc. JUDr. Martina Kubinca, PhD. s názvom „Obchodná spoločnosť v kríze“.